The Fauresmith of South Africa: A new assemblage from Canteen Kopje and significance of the technology in human and cultural evolution. Issue 148 (November 2020) - Kuman, Kathleen; Lotter, Matt G.; Leader, George M.
Abstract: The Fauresmith was a term first coined by archaeologists in the 1920s to describe a cultural development intermediate between the Earlier and Middle Stone Ages. From the late 1960s, many researchers abandoned the term in favor of sinking the Fauresmith within the Later Acheulean. More recently, however, some have supported the idea of the Fauresmith as the earliest Middle Stone Age, whereas other researchers continue to use the term to refer to a transitional technological development. In this article, we evaluate the status of the Fauresmith. We do this by describing a newly excavated assemblage from Canteen Kopje in the Northern Cape Province of South Africa and by comparing it with other assemblages published as Fauresmith. Although there is substantial variability across these assemblages, we present data to show that the relevant assemblages show the consistency of a regional technology that is indeed transitional between the Earlier and Middle Stone Ages. It includes prepared cores, blades, and very reduced numbers of large cutting tools compared with the Acheulean, and it often includes convergent flakes and retouched points. We argue that the Fauresmith, along with parallel developments both within and beyond Africa, is a term worth retaining to identify the slow process of decline of Acheulean technology in favor of a lighter toolkit, which includes varying degrees of more advanced core reduction strategies, larger numbers of formal tools, and hafting. Such developments are associated with populations linked to the development of Homo sapiens in Africa from ca. 600 to 160 ka.